Explaining the evolution of educational attainment in the U.S. - Rui Castro; Daniele Coen-Pirani (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2015)
We study the evolution of educational attainment of the 1932-1972 cohorts using a human capital investment model with heterogeneous learning ability. Inter-cohort variation in schooling is driven by changes in skill prices, tuition, and education quality over time, and average learning ability across cohorts. Under static expectations the model accounts for the main empirical patterns. Rising skill prices for college explain the rapid increase in college graduation till the 1948 cohort. The decline in average learning ability, calibrated to match the evolution of test scores, explains half of the stagnation in college graduation between the 1948 and 1972 cohorts.
Keywords: I24; J24; J31; O11; 330; Educational Attainment; Human Capital; Skill Prices; Inequality; Cohorts; Bildungsabschluss; Männer; USA